2021
DOI: 10.1039/d1tc00628b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast photonics applications based on evanescent field interactions with 2D molybdenum carbide (Mo2C)

Abstract: MXenes have attracted considerable attention for the generation of ultrafast pulsed lasers because of light-matter interactions and excellent saturable absorption characteristics. As a recently developed new member of the MXenes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
11
1
Order By: Relevance
“…The SNR generated in this work was 67.7 dB. It is the highest SNR value compared to Mo 2 C, 73 graphite, 51 MoS 2 , 74 MoTe 2 , 75 PdS 2 , 76 MoSe 2 , 78 MgO, 77 Mxene (Ti 3 C 2 T x ) 79 and SnSe 2 , 80 which clearly indicate that this system is very stable. The pulse width generated using CdTe deposited on D-shaped fiber in this work was 0.77 ps, which was shorter compared to most of those reported in the selected literature studies presented in Table 1 .…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The SNR generated in this work was 67.7 dB. It is the highest SNR value compared to Mo 2 C, 73 graphite, 51 MoS 2 , 74 MoTe 2 , 75 PdS 2 , 76 MoSe 2 , 78 MgO, 77 Mxene (Ti 3 C 2 T x ) 79 and SnSe 2 , 80 which clearly indicate that this system is very stable. The pulse width generated using CdTe deposited on D-shaped fiber in this work was 0.77 ps, which was shorter compared to most of those reported in the selected literature studies presented in Table 1 .…”
Section: Resultsmentioning
confidence: 53%
“…As for the performance of the mode-locked pulses, the result of the current work showed that the generated center wavelength, 1559 nm, was comparable with that from other studies in the C-band region with the wavelength output of our result was slightly lower than that reported in ref. 51 , 73 , 74 , 75 , 76 and 77 but longer than those reported in ref. 78 , 79 and 80 .…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Due to the limitation of experimental conditions, P-scan [34] and Z-scan [40] methods were used to measure the saturable absorption of the Ta 2 NiS 5 -SA. To investigate the nonlinear optical characteristics of the as-fabricated Ta 2 NiS 5 -SA at 1.5 µm, a balanced twindetector measurement system was employed (1550 nm, 600 fs, 7.36 MHz).…”
Section: Saturable Absorption Characteristics Of the Ta 2 Nis 5 -Samentioning
confidence: 99%
“…One way is to deposit the SA material on the fiber connector end facets as a film. The other (evanescent field interactions) is that the material might be deposited on tapered or side-polished fibers [34]. The combination method using side-polished fibers appears to have advantages over the method of depositing materials on the end face of the fiber connector.…”
Section: Introductionmentioning
confidence: 99%